Why are fiscal multipliers asymmetric? The role of credit constraints - Richard McManus; Gulcin Ozkan; Dawid Trzeciakiewicz (2020)
Recent empirical evidence strongly points to the state-dependence of fiscal multipliers which are larger in recessions than in expansions. Yet, standard business cycle models face great difficulty in producing such asymmetric fiscal policy effects. By incorporating endogenously binding collateral constraints into a medium scale DSGE model, we find that fiscal effectiveness can vary substantially across the business cycle. The key to our framework is the state-dependent nature of collateral constraints; binding in bad times while slack in good times, amplifying the effectiveness of fiscal policy and hence generating fiscal multipliers that are larger during recessions.